Spatiotemporal variations of vegetation and its response to climate change and human activities in loess hilly area of western Henan Province, China - Gu, Zhijia; Ji, Keke; Li, Zixin; Xu, Gaohan; Li, Ao; Shen, Yi; Yao, Chong; Yang, Boxiang (Frontiers in Ecology and Evolution, 2025)
IntroductionUnderstanding spatiotemporal variations in vegetation and their climatic and anthropogenic factors can provide a crucial theoretical basis for environmental conservation and ecological restoration in the loess hilly area of western Henan Province. However, the spatiotemporal variation and driving forces of vegetation cover in this area under climate change and human activities are still unclear.MethodsTherefore, in this study, based on the MOD13Q1 NDVI (Normalized Difference Vegetation Index) data from 2000 to 2022, combined with climatic, topographic and human activities data, trend analysis, residual analysis, partial correlation coefficient calculation, and geographical detector techniques were applied to detect the dynamic trends of vegetation changes and their intrinsic relationships with various influencing factors.ResultsThe findings revealed the following: (1) From 2000 to 2022, a comprehensive analysis of satellite-derived vegetation indices revealed substantial enhancements in vegetation cover across 77.5% of the study region, with pronounced improvements documented in five key administrative units: Lushi County, Lingbao City (southern sector), Luoning County, Mianchi County, and Xinan City. In contrast, due to the rapid expansion of urbanization and the implementation of production and construction projects, the vegetation has been greatly disturbed. Severe vegetation degradation has been noted in smaller areas, such as Luoyang City, Mengjin County, Gongyi City, northern Lingbao City, Shangjie District of Rongyang City, and Yiyang County, covering 4.4% of the total area. (2) The seasonal difference of loess hilly area in western Henan is significant. The observed vegetation improvement across the study area between 2000 and 2022 can be primarily attributed to enhanced spring vegetation growth during this period. (3) Partial correlation analysis indicated that the precipitation had more significant effect on NDVI than temperature in the study area. During the study period, the area of pixels with positive NDVI residual trends accounted for 86.96% of the total area. (4) The observed increase in vegetation NDVI across the study area was predominantly attributable to the synergistic effects of climate change and human activities. Landuse, elevation, and temperature exhibited consistently high average explanatory contributions, with each factor independently accounting for over 40%. The explanatory contributions of interaction effects was further enhanced compared to that of individual factors, with the interaction between land use type and elevation reaching as high as 70.9%. The explanatory contributions of various interacting factors on NDVI showed a gradual increase trend.DiscussionThe NDVI changes in the loess hilly region of western Henan exhibit a "promotion-dominated, suppression-supplemented" anthropogenic influence pattern. Human activity intensity serves as the primary driving factor for vegetation changes in this area. For instance, the "Grain for Green Project" has significantly promoted vegetation restoration in the study region, while land use changes tend to trigger substantial vegetation disturbances.